2019
DOI: 10.1073/pnas.1901493116
|View full text |Cite
|
Sign up to set email alerts
|

DeepRiPP integrates multiomics data to automate discovery of novel ribosomally synthesized natural products

Abstract: Microbial natural products represent a rich resource of evolved chemistry that forms the basis for the majority of pharmacotherapeutics. Ribosomally synthesized and posttranslationally modified peptides (RiPPs) are a particularly interesting class of natural products noted for their unique mode of biosynthesis and biological activities. Analyses of sequenced microbial genomes have revealed an enormous number of biosynthetic loci encoding RiPPs but whose products remain cryptic. In parallel, analyses of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 64 publications
1
92
0
Order By: Relevance
“…Genome-mining studies based on these enzymes have revealed that lanthipeptide BGCs are distributed widely across bacterial phyla [21][22][23][24][25][26][27][28][29][30][31][32]. Despite the success in bioinformatically identifying likely lanthipeptide BGCs, it has been an outstanding challenge to perform highthroughput analysis of the precursor peptides encoded in these gene clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-mining studies based on these enzymes have revealed that lanthipeptide BGCs are distributed widely across bacterial phyla [21][22][23][24][25][26][27][28][29][30][31][32]. Despite the success in bioinformatically identifying likely lanthipeptide BGCs, it has been an outstanding challenge to perform highthroughput analysis of the precursor peptides encoded in these gene clusters.…”
Section: Introductionmentioning
confidence: 99%
“…An example for such BGCs is the relatively young but steadily expanding family of ribosomally produced and post-translationally modified peptides (RIPPs), which includes the lantibiotics pinensins (5) and epidermin (6), lassopeptides such as citrocin (7), the antibiotic bottromycins, which feature a unique macoramidine linkage (8,9), and the marine-derived divamides (10), just to name a few. Recently developed bioinformatics tools allow the automated detection of certain classes of RIPPs in bacterial genomes based on signature genes and canonical recognition elements (11)(12)(13)(14)(15)(16). However, the pace of novel RIPPs discovery in recent years suggests that an abundance of yet uncovered RIPP families likely exist.…”
Section: Introductionmentioning
confidence: 99%
“…Another tool recently described, NeuRiPP, is capable of predicting precursors independent of RiPP subclass, but is limited to precursor analysis 30 . Yet another tool, DeepRiPP, can detect novel RiPP BGCs that are chemically far removed from known examples, but is mainly designed to identify new members of known classes 31 . In the end, an algorithm for the discovery of BGCs encoding novel RiPP classes will need to integrate various sources of information to reliably identify genomic regions that are likely to encode RiPP precursors along with previously undiscovered RTEs.…”
Section: Introductionmentioning
confidence: 99%